Analisis Produktivitas Tenaga Kerja dengan Metode Marvin E. Mundel pada CV. Mulia Tata Sejahtera - Adnan Gunawan; Kusnadi Kusnadi; Hamdani Hamdani (Jurnal Serambi Engineering, 2021)
CV. Mulia Tata Sejahtera is a company that produces metal and wood parts using machines such as lathe, milling, drilling and CNC. The company has a production target of 2450 pcs in the 1st period, while the realization of the output produced in the 1st period production process is 2427 pcs. This shows the low level of company productivity. Therefore, this study is aimed at identifying the causes of the low level of productivity by taking into account the resources used. In addition, to provide suggestions for improvements that can be made to increase production efficiency and company productivity. To determine the productivity of CV. Mulia Tata Sejahtera for one period throughout 2020, the measurement of productivity is carried out with Marvin E. Mundel. In this study, three measurement criteria were carried out, namely, labor productivity index, labor absenteeism and production output. The lowest labor productivity index was found in the 6th period with 94.19, while the highest was in the 5th period with 105.98. The lowest labor absentee productivity index was in the 12th period with 69.44, while the highest was in the 6th period with 166.67. The productivity index of the lowest production output level was in the 12th period with 90.97, while the highest was in the 11th period with 110.49. In measuring the company's productivity, the trend is increasing and decreasing or fluctuation.